Image enlargement using biharmonic Said-Ball surface - Saaban, Azizan; Kherd, A; Jameel, A F; Akhadkulov, H; Mohd Alipiah, Fathilah (IOP Publishing, 2017)
This paper discusses the use of biharmonic cubic Said-Ball surfaces in image enlargement area. Resizing an image through up sampling or down sampling is generally common for making smaller image fit a bigger screen in full screen mode or reducing a higher resolution image to a smaller resolution. However due to some limitation, this paper will focus on image enlargement based on scaling factor of two. We use biharmonic cubic Said-Ball subject to a given four boundary curves condition respectively. We implement and evaluate the performance of the proposed method based on peak signal to noise ratio (PSNR) indicator using well-known gray-scale test images.